Gourava and Hyper-Gourava Indices of Some Cactus Chains - Basavanagoud B.; Shruti Policepatil (Journal of the Indonesian Mathematical Society, 2021)
The mathematical chemistry deals with applications of graph theory to study the physicochemical properties of molecules theoretically. A topological index of a graph is a numeric quantity obtained from the graph mathematically. A cactus graph is a connected graph in which no edges lie in more than one cycle. In this paper, we compute Gourava and hyper-Gourava indices of some cactus chains.